2010
DOI: 10.1093/nar/gkq022
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent probes for the analysis of DNA strand scission in base excision repair

Abstract: We have developed fluorescent probes for the detection of strand scission in the excision repair of oxidatively damaged bases. They were hairpin-shaped oligonucleotides, each containing an isomer of thymine glycol or 5,6-dihydrothymine as a damaged base in the center, with a fluorophore and a quencher at the 5′- and 3′-ends, respectively. Fluorescence was detected when the phosphodiester linkage at the damage site was cleaved by the enzyme, because the short fragment bearing the fluorophore could not remain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…1D, the method was found to be capable of detecting UDG activity as low as 0.0008 U mL À1 based on 3s b /S, in a range of at least 0.0008-0.1 U mL À1 . This sensitivity was comparable or even better than those in the previously reported fluorescent methods for UDG activity assays, [13][14][15][16][17][18][19][20][21][25][26][27]34 most probably ascribed to its characteristics of one uracil removal in each DNA substrate without the need of DNA conformational changes. The results of polyacrylamide gel electrophoresis (PAGE) and matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) analysis on the DNA duplex in the absence and presence of UDG clearly showed that the uracil in DNA-U was removed by UDG regardless of the presence of DNA-X or ATMND (Fig.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…1D, the method was found to be capable of detecting UDG activity as low as 0.0008 U mL À1 based on 3s b /S, in a range of at least 0.0008-0.1 U mL À1 . This sensitivity was comparable or even better than those in the previously reported fluorescent methods for UDG activity assays, [13][14][15][16][17][18][19][20][21][25][26][27]34 most probably ascribed to its characteristics of one uracil removal in each DNA substrate without the need of DNA conformational changes. The results of polyacrylamide gel electrophoresis (PAGE) and matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) analysis on the DNA duplex in the absence and presence of UDG clearly showed that the uracil in DNA-U was removed by UDG regardless of the presence of DNA-X or ATMND (Fig.…”
supporting
confidence: 55%
“…12 For instance, pairs of fluorophores and quenchers were attached at the ends of uracil-containing DNA substrates to measure UDG activity via fluorescence enhancement. [13][14][15] Nanomaterials including graphene oxide and gold nanoparticles were also utilized as quenchers and colorimetric reporters, respectively, for optical UDG assays. 16,17 Besides, the activation of uracil-containing DNAzymes by UDG was applied for more sensitive detection of UDG activity through DNAzyme-based signal amplifications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This basic strategy contrasts with the uracil-directed, tethered ligand strategy developed by the Stivers group for discovery of UDG2 inhibitors [34], or the hairpin strategy utilized by the Iwai group for probing cellular BER activity [35]. While these models were efficient in the identification of novel inhibitors [36], [37] and allowed for detection of glycosylase activity, neither approach was designed or adapted to probe large libraries of small molecules as part of a high-throughput screen.…”
Section: Resultsmentioning
confidence: 99%
“…We then protected both hydroxyl groups of the thymine glycol with acetyl groups. [20,21] The resulting compounds 3a, 3b were treated with trifluoroacetic acid to give the 5,6- O -acetyl-2′-ribofluorothymidine glycols 4a, 4b which were converted to the phosphoramidite building blocks 6a, 6b by standard procedures.…”
Section: Resultsmentioning
confidence: 99%